389 In vitro dry matter digestibility of multiple sources of microalgae and microalgae products for growing pigs. (1st March 2017) - Hanson, B. W.; Zeng, Z. K.; Shurson, G. C.; Ruan, R.; Chen, C.; Urriola, P. E.
Abstract: Use of microalgae in agricultural application has substantially increased in recent years. To evaluate the relative nutritional value of microalgae products, it is necessary to have an estimate of the nutrient digestibility. In vitro procedures are a good alternative to model processes of nutrient digestion in the gastrointestinal tract of pigs. The objective of this project was to measure the nutrient composition and in vitro DM digestibility (IVDMD) of different microalgae sources. Four microalgae samples were obtained from multiple agricultural sources: 1) microalgae ( Chlorella sp.) grown in waste water from a dairy processing plant, 2) microalgae ( Chlorella sp.) grown in waste water from a meat processing plant, 3) protein and lipid extracted microalgae product grown for biofuels production, and 4) microalgae ( Pavlova sp.) grown in microalgae-specific media. The IVDMD was measured using a 2-step technique. First, triplicate samples from each source (1 g) were incubated in a 7:1 mixture of potassium phosphate– and sodium phosphate–based buffer solutions (pH 2) with 2 mL (100 mg/mL) of fresh pepsin solution for 2 h at 39°C. Immediately after gastric hydrolysis, small intestinal hydrolysis was performed by adjusting solution pH to 6.8 by adding a 1:1 mixture of potassium phosphate– and sodium phosphate–based buffer solutions and adding 2 mL of pancreatin solution (100 mg/mL). After 4 h of hydrolysis at 39°C, all samples were centrifuged at 10, 000 g for 10 min and supernatant was removed. The pellet after centrifugation was dried at 55°C for 48 h and the weight was recorded. The IVDMD was calculated as a ratio between DM before and after hydrolysis. The IVDMD of Pavlova sp. (50.7 ± 0.5%) was less ( P < 0.05) than that of Chlorella sp. grown in dairy waste water (57.1 ± 0.1%), which was greater than that of Chlorella sp. grown in meat processing waste water (64.2 ± 0.9%). The greatest IVDMD was observed in the protein and lipid extracted microalgae product (80.2 ± 4.9%). Digestibility values of microalga grown in dairy waste water and grown in meat processing waste water were not different ( P > 0.05) from ground corn (62.6 ± 2.7%) used as control. In conclusion, microalgae products from various industrial application may have significantly different nutritional values to growing pigs because they have different digestibility values.